Synthesis and reactivity of heteroleptic zinc(i) complexes toward heteroallenes. Issue 100 (29th November 2021) - Li, Bin; Huse, Kevin; Wölper, Christoph; Schulz, Stephan
Abstract : Heteroleptic zinc(i ) complexes Cp*Zn–ZnL 1/2 were synthesized and reactions of Cp*Zn–ZnL 2 2 with t -BuNCO and organoazides RN3 proceeded with insertion into the Zn–Zn bond and formation of novel zinc carbamate, bis-hexazene, triazenide, and azide complexes 4–7 . Abstract : Heteroleptic zinc(i ) complexes L 1, 2 Zn–ZnCp* (L 1 = HC[C(CF3 )NC6 F5 ]2 1 ; L 2 = HC[C(Me)NDipp]2 ; Dipp = 2, 6-i-Pr2 C6 H3 2 ) are synthesized by reactions of Cp*2 Zn2 with L 1 H and L 2 ZnH. 2 reacts with t -BuNCO to give unprecedented carbamate complex (4 ), while reactions with RN3 gave bis-hexazene, triazenide, and trimeric azide complexes (5–7 ).